IMPLEMENTASI PEMBIASAAN MEMBACA PERKALIAN PRA PEMBELAJARAN UNTUK MENUMBUHKAN KARAKTER DISIPLIN SISWA DI MADRASAH IBTIDAIYAH - Maghfiroh, Ummi Lailatul; Muji Lestari, Titis Wahyu; Siswanto, Hervi Madadina (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study examines the implementation of pre-learning multiplication reading habituation as a strategy to develop discipline character in Madrasah Ibtidaiyah students. Using a qualitative case study approach, the research was conducted at a private Madrasah Ibtidaiyah from September to October 2025, involving 20 third-grade students, 4 classroom teachers, and 1 school coordinator. Data were collected through non-participant observation, semi-structured interviews, and document analysis, then analyzed using an interactive model with triangulation techniques. The findings reveal that multiplication reading habituation implemented routinely every Friday morning for 10-15 minutes successfully cultivates both time discipline and learning discipline in students. Punctuality increased significantly from 55% to 95% over eight weeks, while adherence to instructions reached 93% and learning readiness achieved 90%. Supporting factors include teacher consistency as role models, positive reinforcement, leadership role rotation, and synergy between school and family environments. Hindering factors include time limitations, variations in student abilities, and occasional concentration disturbances, which teachers overcame through adaptive strategies. This research demonstrates that simple academic habituation, when implemented consistently, can effectively serve as character education media without requiring large costs or advanced technology. The study contributes to character education theory and practice in Islamic elementary education contexts, providing concrete guidelines for integrating discipline values with daily learning activities.